Black people’s right to the city: from a racist sociospatial formation toward a lefebvrian utopia - Rezende, Ana Flávia; Andrade, Luís Fernando Silva [UNESP] (FapUNIFESP (SciELO), 2022)
The right to the city manifests itself as a superior form of rights in the participation and appropriation of urban spaces. In the present text, we argue that the black population, as individuals and collectives with mutilated citizenship, manifests cumulative disadvantages that prevent them from exercising full citizenship and disputing the city. This situation does not appear as fatalism, since the resistance of black people is widely discussed in the literature of social movements. The objective of this article is to propose developments between Henri Lefebvre's right to the city and the racial issue. To this end, we present topics dealing with race and segregation, right to the city and utopia, and racialization of the right to the city. We conclude that to consider the dimension of race in the right to the city is to spatialize the racial issue, since to contemplate a city read from a racial perspective is not only relevant from an academic point of view, but also as an exercise in unveiling oppressive realities and as part of the very counter-space that is the right to the city.
Direito do Negro à Cidade: de uma Formação Socioespacial Racista à Utopia Lefebvriana
Keywords: Intersectionality; Race; Right to the City; Sociospatial Formation